Capillary filling in microchannels patterned by posts. - Mognetti, B; Yeomans, J (2009)
We investigate the capillary filling of three-dimensional microchannels with surfaces patterned by posts of square cross section. We show that pinning on the edges of the posts suppresses and can halt capillary filling. We stress the importance of the channel walls in controlling whether filling can occur. In particular for channels higher than the distance between adjacent posts, filling occurs for contact angles less than a threshold angle of approximately 55 degrees , independent of the height of the channel.